What finance for what investment? Survey-based evidence for European companies - Annalisa Ferrando; Carsten Preuss (European Investment Bank (EIB), 2018)
We examine the link between corporate financing and investment decisions of European firms by using a novel firm-level survey of the European Investment Bank (EIBIS). The survey provides rich quantitative information of a wide range of financing sources and tangible and intangible investment types for a representative sample of EU28 firms in 2016. We provide new evidence and contribute to previous research in the following ways: first we consider the heterogeneous effect of internal and external finance on different tangible and intangible investment types. Second, our analysis focuses on a broad spectrum of nonfinancial corporations across size classes from different countries. By using a multinomial fractional response model to estimate the finance-investment link, we find that SMEs and large enterprises show a different financing behaviour for their investment activity. The results suggest that SMEs' tangible asset investment is positively related to the use of bank finance, whereas internal finance is preferred for intangible asset investments.
Keywords: D22; E22; G32; L25; 330; tangible and intangible investment; internal and external finance; R&D investment; SME finance; multivariate fractional response model